2021
DOI: 10.3389/fonc.2021.718578
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Abnormal TSHR Signaling Activation and PTEN/PI3K in the Dedifferentiation of Thyroid Cancer Cells

Abstract: Iodide uptake and the metabolism of thyroid cells are regulated by thyrotropin (TSH)-TSH receptor (TSHR) signaling. Thus, it is necessary to elevate serum TSH levels by T4 withdraw or rTSH administration to facilitate radioiodide (131I) therapy for differentiated thyroid cancer (DTC). However, non-iodide-avid metastases of DTC which is dedifferentiated do not respond to stimulation by high levels of TSH, suggesting abnormal TSH-TSHR signal transduction in cancer cells. In addition, PI3K/AKT/mTOR signaling acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…( Figure 1d ). This low expression has also been verified by other groups [23,27,28,40]; while some others even cite TSHR expression as undetectable [4143]. Low TSHR expression allows only for limited stimulation by circulating TSH molecules and this was theorized to be a great limitation of the hormone’s role study.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…( Figure 1d ). This low expression has also been verified by other groups [23,27,28,40]; while some others even cite TSHR expression as undetectable [4143]. Low TSHR expression allows only for limited stimulation by circulating TSH molecules and this was theorized to be a great limitation of the hormone’s role study.…”
Section: Resultsmentioning
confidence: 59%
“…Herein, we investigated for the first time the effects of rh-TSH in physiologically relevant doses resembling the TSH concentrations in human plasma on the function and proliferation of PTC human thyroid cell lines. For this purpose, we selected two well established cell lines, K1 and TPC-1, both of which adequately model PTC cells and express the main thyroid markers, thus allowing their classification as PTC cells and indicting their differentiation status [27,28]. To fully assess the role of rh-TSH in PTC cell proliferation, not only did we co-administer it with recombinant human insulin (rh-INS), but we also created cells that controllably overexpress the TSH receptor.…”
Section: Introductionmentioning
confidence: 99%
“…TSH has also been shown to promote vascular endothelial growth factor production thus contributing to angiogenesis ( 75 , 76 ) to induce genomic instability ( 77 ) and to contribute to invasion and immune evasion in thyroid tumors ( 78 ). Conversely, the TSH-R seems to have an important role in maintaining differentiation of thyroid cancer cells, and in advanced and dedifferentiated thyroid cancer, a decrease in its expression has commonly been reported ( 79 ).…”
Section: Tsh Receptor In Human Diseasementioning
confidence: 99%
“…Among these effector molecules, AKT is the most studied and universally activated molecule downstream of PI3Ks ( 9 ). Studies have reported that TSAb can regulate the proliferation activity of thyroid cells via the PI3K/AKT pathway ( 10 , 11 ). Chinese medicine for hyperthyroidism primarily modulates the proliferation and apoptosis of thyroid cells through regulation of the PI3K/AKT pathway to effectively treat GD ( 12 - 14 ).…”
Section: Introductionmentioning
confidence: 99%